Development of a cost‐effective single nucleotide polymorphism genotyping array for management of greater yam germplasm collections. Issue 10 (29th April 2019) - Cormier, Fabien; Mournet, Pierre; Causse, Sandrine; Arnau, Gemma; Maledon, Erick; Gomez, Rose‐Marie; Pavis, Claudie; Chair, Hâna
Abstract: Using genome‐wide single nucleotide polymorphism (SNP) discovery in greater yam ( Discorea alata L.), 4, 593 good quality SNPs were identified in 40 accessions. One hundred ninety six of these SNPs were selected to represent the overall dataset and used to design a competitive allele specific PCR array (KASPar). This array was validated on 141 accessions from the Tropical Plants Biological Resources Centre (CRB‐PT) and CIRAD collections that encompass worldwide D. alata diversity. Overall, 129 SNPs were successfully converted as cost‐effective genotyping tools. The results showed that the ploidy levels of accessions could be accurately estimated using this array. The rate of redundant accessions within the collections was high in agreement with the low genetic diversity of D. alata and its diversification by somatic clone selection. The overall diversity resulting from these 129 polymorphic SNPs was consistent with the findings of previously published studies. This KASPar array will be useful in collection management, ploidy level inference, while complementing accurate agro‐morphological descriptions. Abstract : A SNP genotyping array was developed and validated on 141 greater yam accessions from the Tropical Plants Biological Resources Centre (CRB‐PT) and CIRAD collections. This array provides an overview of the diversity consistent with the previously published studies and allows to accurately estimate ploidy levels. Regarding clonality issues, the importance of vegetative reproduction and somaclonal selection in D. alata, it is a complementary tool to a good agro‐morphological description of collections.